Lithium-sulfur battery composite positive electrode and lithium-sulfur battery

By designing a composite barrier layer on the positive electrode of the lithium sulfur battery, it effectively blocks the diffusion of polysulfides, solves the problems caused by the shuttle effect of polysulfides in lithium sulfur batteries, and improves the cycle stability and energy density of the battery.

CN119495704AActive Publication Date: 2025-02-21SICHUAN UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510059678.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-02-21
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

In practical applications, lithium-sulfur batteries face redox side reactions caused by polysulfide shuttle effect and corrosion of metal lithium negative electrodes, which affect the cycle stability and energy density of the battery.

Method used

A composite positive electrode structure is adopted, including a positive electrode current collector, a carbon-sulfur composite material layer and a composite barrier layer. The composite barrier layer is composed of a TiO2-graphene layer and a SiO2-carbon nanotube layer, which effectively blocks the diffusion of polysulfides through these layers.

Benefits of technology

Effectively inhibit the shuttle effect of polysulfides, improve the cycle stability, energy density and safety of the battery, and extend the service life of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of lithium-sulfur secondary batteries, and relates to a lithium-sulfur battery composite positive electrode and a lithium-sulfur battery, the composite positive electrode comprises a positive electrode current collector, a carbon-sulfur composite material layer located on the positive electrode current collector and a composite barrier layer located on the carbon-sulfur composite material layer, the composite barrier layer is composed of a TiO2-graphene layer close to the carbon-sulfur composite material layer and a SiO2-carbon nanotube layer located on the TiO2-graphene layer, and the thickness of the TiO2-graphene layer is smaller than that of the SiO2-carbon nanotube layer. By arranging the specific composite barrier layer, the shuttle effect of polysulfide can be effectively inhibited, the loss of a sulfur positive electrode material is effectively prevented, more active sulfur is ensured to participate in electrochemical reaction, side reaction between an electrode material and electrolyte is prevented, the increase of interface impedance is reduced, and the thickness of the electrode is not excessively increased; the transmission efficiency of lithium ions is influenced or inactive components are increased, so that the energy density and the capacity retention ratio of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium-sulfur secondary batteries, and in particular relates to a lithium-sulfur battery composite positive electrode and a lithium-sulfur battery. The composite positive electrode can effectively inhibit the polysulfide shuttle effect and improve the cycle stability and energy density of the battery. Background Art

[0002] With the advancement of new energy vehicle technology and its huge market potential, modern society is extremely eager for advanced high-energy storage devices with low cost, high safety and environmental friendliness. The key to the development of electric vehicles lies in batteries. The lithium-ion battery technology of the widely used lithium iron phosphate battery and ternary positive electrode materials has made great progress. However, due to the limitations of the theoretical lithium storage capacity of the positive and negative electrode materials themselves, it is difficult to achieve a major breakthrough in the energy density of commercial traditional lithium-ion batteries. Metal lithium has low density, high electronegativity, and high theoretical specific capacity (3860 mAh g -1 ) has become the preferred negative electrode material in the rechargeable battery system. Compared with the current mainstream ternary NCM lithium-ion battery, the battery with sulfur positive electrode has a theoretical specific energy of up to 2600 Wh kg -1 , which is more than 10 times that of the currently widely used lithium-ion batteries. At the same time, sulfur has the advantages of abundant natural reserves, high theoretical specific capacity, and green and pollution-free. It can be selected as a positive electrode material and lithium negative electrode to form a lithium-sulfur battery system. Commercial lithium-sulfur battery energy equipment will be a great progress in the development of human science and technology.

[0003] Although lithium-sulfur batteries have significant theoretical advantages, their practical application still faces many challenges. First, the initial product of lithium-sulfur battery discharge - long-chain polysulfides are easily soluble in commonly used ether electrolytes, providing a medium for the dissolution, diffusion and shuttling of polysulfides between electrodes. This shuttling effect leads to the occurrence of redox side reactions and the corrosion of the metal lithium negative electrode, which greatly affects the coulombic efficiency and specific capacity retention rate of the lithium-sulfur battery system. In recent years, researchers have explored a variety of methods to inhibit the diffusion and shuttling of lithium polysulfides. For example, CN118017049A discloses a lithium-sulfur battery intermediate layer material, the intermediate layer material includes: a conductive substrate layer and a catalytic layer attached to at least part of the surface of the conductive substrate layer, the catalytic layer includes a nanostructured oxide and a manganese oxide, the nanostructured oxide is attached to the conductive substrate layer, the manganese oxide is attached to at least part of the surface of the nanostructured oxide, and there is a heterogeneous structure interface layer between the manganese oxide and the nanostructured oxide; the catalytic activity is improved by forming a heterogeneous structure between the manganese oxide and the nanostructured oxide, and the oxide has higher stability than the sulfide. By utilizing the conductivity of the conductive matrix and the good anchoring ability of the catalytic layer for polysulfides, the polysulfide intermediates are effectively captured while accelerating their redox kinetics, thereby alleviating the shuttling effect of polysulfides. CN116845352A discloses a method for preparing a covalent organic framework-enhanced gel electrolyte for lithium-sulfur batteries. The gel electrolyte greatly reduces the amount of electrolyte, inhibits the dissolution of lithium polysulfide into the electrolyte, and ensures high ionic conductivity and lithium ion migration number. CN111370667A discloses a three-dimensional ordered porous sulfur-carrying material for the positive electrode of a lithium-sulfur battery. The template method and the solvent induction method are combined to make the positive electrode sulfur-carrying material uniformly and orderly distributed with macropores, and these ordered macropores are connected by a framework containing rich micropores and mesoporous structures. In this porous conductive framework, polar site zinc sulfide and single-atom active site Co-NC are widely distributed to fix the polysulfide intermediates produced during the electrochemical reaction to reduce the problem of rapid capacity decay caused by its "shuttle effect". CN117335094A discloses a method for preparing a high-entropy single-atom catalyst modified diaphragm, wherein different soluble metal salts are mixed with carbon and nitrogen compounds and subjected to heat treatment to obtain a precursor, and then the metal atoms on the precursor are transferred to a nitrogen-doped carbon carrier by high-temperature argon treatment to obtain a high-entropy single-atom catalyst, which can be used as a modified material for the diaphragm in a lithium-sulfur battery. The high-entropy single-atom catalyst modified diaphragm prepared by the method greatly improves the wettability of the diaphragm to the electrolyte, and is used in lithium-sulfur batteries to accelerate the kinetics of the redox reaction of sulfur and inhibit the shuttle effect.

[0004] However, due to the weak interaction of conventional materials, the adsorption capacity of polysulfides is limited, and a high degree of inhibition of the shuttle effect cannot be achieved. Simply setting a barrier layer on the surface of the positive and negative electrode materials may affect the transmission of lithium ions and produce more defects, leading to the risk of short circuits, which in turn affects the performance of lithium-sulfur batteries. In addition, the introduction of thicker barrier layers or more inactive carrier materials will also reduce the specific energy of the positive electrode itself. Therefore, it is necessary to develop a composite positive electrode for lithium-sulfur batteries. For example, by simply adjusting the structure or composition of the positive electrode layer, the polysulfide shuttle effect can be effectively blocked, thereby improving the cycle stability, energy density and safety of lithium-sulfur batteries, and improving the commercial application prospects of lithium-sulfur batteries. Summary of the invention

[0005] In order to solve the defects in the prior art, the present invention provides a lithium-sulfur battery composite positive electrode and a lithium-sulfur battery. The composite positive electrode comprises a positive electrode current collector, a carbon-sulfur composite material layer on the positive electrode current collector, and a composite barrier layer on the carbon-sulfur composite material layer. The composite barrier layer is composed of TiO 2 -Graphene layer and on TiO 2 -SiO on graphene layer 2 -carbon nanotube layer, the composite barrier layer can effectively block the diffusion of polysulfide. First, TiO 2 - The graphene layer serves as the first barrier. Titanium dioxide has high chemical stability and ion selectivity, which can prevent the diffusion of polysulfides from the positive electrode to the electrolyte, while graphene provides good conductivity and mechanical strength to ensure smooth electron transmission paths. SiO 2 It has excellent chemical stability and hydrophobicity, and can effectively prevent the penetration of polysulfides, while carbon nanotubes provide additional conductive channels to ensure the efficient transmission of lithium ions. The setting of this layer further enhances the blocking effect on polysulfides. At the same time, the double-layer barrier material has good chemical stability and mechanical strength, and can form a stable electrode / electrolyte interface in the battery, effectively preventing side reactions between the electrode material and the electrolyte, reducing the increase in interface impedance, thereby improving the electrochemical performance of the battery, and then improving the battery's cycle stability and coulomb efficiency.

[0006] To achieve the above-mentioned object of the present invention, the present invention provides a lithium-sulfur battery composite positive electrode, which comprises a positive electrode current collector, a carbon-sulfur composite material layer located on the positive electrode current collector, and a composite barrier layer located on the carbon-sulfur composite material layer, wherein the composite barrier layer is composed of TiO 2 -Graphene layer and on TiO 2 -SiO on graphene layer 2 -Carbon nanotube layer composition.

[0007] Furthermore, the TiO 2-The graphene layer thickness is 0.05~5μm, the SiO 2 -The thickness of the carbon nanotube layer is 0.1 μm to 5 μm, and the TiO 2 - The graphene layer thickness is smaller than the SiO 2 -Thickness of the carbon nanotube layer. The setting of the specific thickness of the composite barrier layer can first ensure that the barrier layer can effectively block the diffusion of polysulfides. The composite barrier layer can achieve complete adsorption catalysis of polysulfides without excessively increasing the thickness of the positive electrode layer and affecting the transmission efficiency of lithium ions. At the same time, the reasonable thickness control of the present invention allows the electrode / electrolyte interface to maintain good contact, ensuring the high-efficiency operation of the battery.

[0008] Furthermore, the thickness of the carbon-sulfur composite material layer is 200-500 μm, and the mass ratio of nano-sulfur to conductive carbon black in the layer is 5-10: 1. The sulfur content in the positive electrode of the lithium-sulfur battery of the present invention is high, the specific capacity is high, and the battery has a large energy density.

[0009] Furthermore, the TiO 2 -TiO in graphene layer 2 The mass ratio of SiO to graphene is 1:2~5. 2 -SiO in carbon nanotube layer 2 The mass ratio of TiO to carbon nanotubes is 2~5:1. 2 - The graphene layer has a higher carbon content, which can achieve rapid charge transfer, while the SiO2 far away from the carbon-sulfur composite layer 2 -The carbon content of the carbon nanotube layer is relatively low, but the carbon nanotubes can also realize charge transfer along a specific path, and the lower carbon content of this layer can also improve the insulation performance between the positive and negative electrodes to a certain extent.

[0010] Furthermore, the carbon-sulfur composite material layer is composed of elemental sulfur, conductive carbon black and a binder, and the preparation method is as follows: Add elemental sulfur, conductive carbon black and a binder into an organic solvent, mix well to obtain a positive electrode slurry, apply the positive electrode slurry on a positive electrode collector, and dry in vacuum at 80-100° C. to form a carbon-sulfur composite material layer on the surface of the positive electrode collector; the mass ratio of the elemental sulfur, conductive carbon black and binder is 5-10:1:0.5-1.

[0011] Furthermore, the TiO 2 -The graphene layer preparation method is as follows: TiO 2 The particles, graphene nanosheets and binder are added to an organic solvent, mixed to obtain a slurry, the slurry is coated on the carbon-sulfur composite material layer, and vacuum dried at 100-150° C. to obtain the TiO 2The mass ratio of particles, graphene nanosheets and binder is 1:2~5:0.5~1.

[0012] Furthermore, the SiO 2 -The carbon nanotube layer preparation method is as follows: SiO 2 The particles, carbon nanotubes and binder are added to an organic solvent and mixed to obtain a slurry, and the slurry is coated on the TiO 2 -graphene layer, and dried in air at 100-150°C to obtain the SiO 2 The mass ratio of particles, carbon nanotubes and binder is 2~5:1:0.5~1.

[0013] Further, the carbon-sulfur composite material layer, TiO 2 -Graphene layer and SiO 2 -The same organic solvent and binder are used in the carbon nanotube layer. The use of the same binder can ensure good bonding between the layers. The binder forms a uniform interface between the layers, enhances the adhesion between the layers, and prevents the occurrence of interlayer peeling or delamination. At the same time, it can also reduce the defects between the interfaces of the layers, ensure seamless connection between the materials of each layer, and reduce the interface impedance. Preferably, the binder is one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose-styrene butadiene rubber, and polyvinyl alcohol, and the organic solvent is one of N-methylpyrrolidone, acetonitrile, and acetone.

[0014] Another object of the present invention is to provide a lithium-sulfur battery, the lithium-sulfur battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, the positive electrode being a composite positive electrode comprising a positive electrode current collector, a carbon-sulfur composite material layer on the positive electrode current collector and a composite barrier layer on the carbon-sulfur composite material layer, the composite barrier layer comprising TiO2 adjacent to the carbon-sulfur composite material layer and a plurality of layers of the composite barrier layer. 2 -Graphene layer and on TiO 2 -SiO on graphene layer 2 -Carbon nanotube layer composition.

[0015] The present invention also provides a method for preparing a lithium-sulfur battery composite positive electrode, comprising the following steps: 1) Preparation of a carbon-sulfur composite material layer: adding elemental sulfur, conductive carbon black and a binder in a mass ratio of 5-10:1:0.5-1 to an organic solvent, mixing well to obtain a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector aluminum foil, and vacuum drying at 80-100° C. to form a carbon-sulfur composite material layer of 200-500 μm thick on the surface of the aluminum foil; 2) Preparation of TiO 2 -Graphene layer: TiO 2The particles, graphene nanosheets, and a binder are added to an organic solvent and mixed to obtain a slurry, which is coated on the carbon-sulfur composite material layer and dried in a vacuum at 100-150° C. to form a 0.05-5 μm thick TiO 2 - graphene layer; 3) Preparation of SiO 2 - Carbon nanotube layer: SiO 2 The particles, carbon nanotubes and binder are added to an organic solvent and mixed to obtain a slurry, and the slurry is coated on the TiO 2 -graphene layer, dried in air at 100~150℃, on TiO 2 - The graphene layer is formed on the TiO 2 - Graphene layer thickness of 0.1μm~5μm SiO 2 - a carbon nanotube layer; The binder is one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose-styrene butadiene rubber, and polyvinyl alcohol, and the organic solvent is one of N-methyl pyrrolidone, acetonitrile, and acetone. The preparation method of the composite positive electrode adopts a simple slurry coating process, and each layer of material is mixed and coated on the positive electrode current collector or the previous layer of material, and then dried. This process is simple and easy, suitable for large-scale industrial production, and reduces manufacturing costs. The same binder and dispersing solvent can ensure that each layer of slurry has similar rheological properties, so that each layer of material can be evenly distributed during the coating process, avoiding the problem of local accumulation or uneven thickness.

[0016] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: 1. The double-layer composite barrier layer with a specific composition can effectively inhibit the polysulfide shuttle effect, effectively prevent the loss of sulfur positive electrode materials, ensure that more active sulfur participates in the electrochemical reaction, and improve the energy density and capacity retention rate of the battery. Titanium dioxide and silicon dioxide in the composite barrier layer can effectively prevent the diffusion of polysulfides from the positive electrode to the electrolyte, so that the shuttle effect of polysulfides is greatly inhibited. Both graphene and carbon nanotubes have excellent electrical conductivity and can significantly improve the overall conductivity of the electrode without affecting the transmission of lithium ions, thereby improving the cycle stability, coulomb efficiency and rate performance of the battery; 2. The introduction of the composite barrier layer forms a stable electrode / electrolyte interface, which can effectively prevent the side reaction between the electrode material and the electrolyte, reduce the increase of the interface impedance, and thus improve the electrochemical performance of the battery. The design of the two layers with specific thickness enables the electrode / electrolyte interface to maintain good contact, ensuring that the barrier layer can effectively block the diffusion of polysulfides without excessively increasing the thickness of the electrode, affecting the transmission efficiency of lithium ions or causing the increase of inactive components to affect the specific energy of the battery.

[0017] 3. In addition, the setting of the composite barrier layer can also prevent the loss of sulfur positive electrode active materials, ensure that more active sulfur participates in the electrochemical reaction, and improve the energy density and capacity retention rate of the battery. In addition, the composite barrier layer can also reduce the impact of the volume expansion of the electrode material on the battery structure, further extending the service life of the battery. DETAILED DESCRIPTION

[0018] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0019] It should be noted that the reference to "embodiment" in this document means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0020] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.

[0021] The performance test of the lithium-sulfur battery in the present invention is carried out by assembling a 2032 lithium-sulfur button cell. Specifically, the prepared composite positive electrode is cut into a small disc with a diameter of 12 mm, and then a commercial lithium sheet of the same size is used as the negative electrode. The electrolyte is 1 mol lithium bistrifluoromethylsulfonyl imide (LiTFSI) and 0.1 mol / L lithium nitrate (LiNO 3 ) 1,3-dioxolane / ethylene glycol dimethyl ether (DOL / DME, volume ratio of 1:1) solution, Celgard 2400 as separator, assembled into 2032 button cells. The specific assembly method is: place the composite positive electrode in the positive electrode shell, add 100 mL of electrolyte, put in the separator, then place the negative electrode on the separator, add the gasket spring and the negative electrode shell on the negative electrode in turn, and finally press the positive electrode shell and the negative electrode shell together under a pressure of 50 MPa to obtain a 2032 button cell.

[0022] Example 1

[0023] A lithium-sulfur battery composite positive electrode, the preparation method is as follows: 1) Preparation of a carbon-sulfur composite material layer: adding elemental sulfur, conductive carbon black and binder polyvinylidene fluoride in a mass ratio of 5:1:0.5 to an organic solvent N-methylpyrrolidone, mixing well to obtain a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector aluminum foil, and vacuum drying at 80° C. to form a 200 μm thick carbon-sulfur composite material layer on the surface of the aluminum foil; 2) Preparation of TiO 2 -Graphene layer: TiO 2 The particles, graphene nanosheets, and binder polyvinylidene fluoride are added to an organic solvent N-methylpyrrolidone, and mixed to obtain a slurry. The slurry is coated on the carbon-sulfur composite material layer and vacuum dried at 100°C to form a 0.05 μm thick TiO 2 - graphene layer; 3) Preparation of SiO 2 - Carbon nanotube layer: SiO 2 The particles, carbon nanotubes, and binder polyvinylidene fluoride are added to an organic solvent N-methylpyrrolidone, mixed to obtain a slurry, and the slurry is coated on the TiO 2 -graphene layer, dried in air at 100 °C, on TiO 2 -0.1μm SiO is formed on the graphene layer 2 - Carbon nanotube layer.

[0024] The lithium-sulfur battery using the composite cathode was tested, and the first cycle discharge capacity was 1159 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 92.2%; the first cycle discharge capacity at a rate of 2C is 970mAhg -1 , the capacity retention rate is higher than 85% after 1000 cycles.

[0025] Example 2

[0026] A lithium-sulfur battery composite positive electrode, the preparation method is as follows: 1) Preparation of a carbon-sulfur composite material layer: adding elemental sulfur, conductive carbon black and binder carboxymethyl cellulose-styrene-butadiene rubber in a mass ratio of 10:1:1 to an organic solvent acetone, mixing well to obtain a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector aluminum foil, and vacuum drying at 100° C. to form a 500 μm thick carbon-sulfur composite material layer on the surface of the aluminum foil; 2) Preparation of TiO 2 -Graphene layer: TiO 2The particles, graphene nanosheets, and binder carboxymethyl cellulose-styrene butadiene rubber were added to an organic solvent acetone and mixed to obtain a slurry. The slurry was coated on the carbon-sulfur composite material layer and vacuum dried at 150°C to form a 4.5 μm thick TiO 2 - graphene layer; 3) Preparation of SiO 2 - Carbon nanotube layer: SiO 2 The particles, carbon nanotubes, and binder carboxymethyl cellulose-styrene butadiene rubber are added to an organic solvent acetone and mixed to obtain a slurry. The slurry is coated on the TiO 2 -graphene layer, dried in air at 150 °C, on TiO 2 -5μm SiO2 is formed on the graphene layer 2 - Carbon nanotube layer.

[0027] The lithium-sulfur battery using the composite cathode was tested and the first cycle discharge capacity was 1241 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 98.3%; the first cycle discharge capacity at a rate of 2C is 1016mAhg -1 , the capacity retention rate is higher than 90% after 1000 cycles.

[0028] Example 3

[0029] A lithium-sulfur battery composite positive electrode, the preparation method is as follows: 1) Preparation of a carbon-sulfur composite material layer: adding elemental sulfur, conductive carbon black and binder polytetrafluoroethylene in a mass ratio of 8:1:1 to an organic solvent acetonitrile, mixing well to obtain a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector aluminum foil, and vacuum drying at 90° C. to form a 300 μm thick carbon-sulfur composite material layer on the surface of the aluminum foil; 2) Preparation of TiO 2 -Graphene layer: TiO 2 The particles, graphene nanosheets, and binder polytetrafluoroethylene are added to the organic solvent acetonitrile and mixed to obtain a slurry. The slurry is coated on the carbon-sulfur composite material layer and vacuum dried at 120°C to form a 1.5 μm thick TiO 2 - graphene layer; 3) Preparation of SiO 2 - Carbon nanotube layer: SiO 2 The particles, carbon nanotubes and binder polytetrafluoroethylene are added to the organic solvent acetonitrile and mixed to obtain a slurry. The slurry is coated on the TiO 2 -graphene layer, dried in air at 120 °C, on TiO 2 -3μm SiO2 is formed on the graphene layer2 - Carbon nanotube layer.

[0030] The lithium-sulfur battery using the composite cathode was tested, and the first cycle discharge capacity was 1193 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 96.1%; the first cycle discharge capacity at a rate of 2C is 992mAhg -1 , the capacity retention rate is higher than 88% after 1000 cycles.

[0031] Example 4

[0032] A lithium-sulfur battery composite positive electrode, the preparation method is as follows: 1) Preparation of a carbon-sulfur composite material layer: adding elemental sulfur, conductive carbon black and binder polyvinyl alcohol in a mass ratio of 6:1:1 to an organic solvent N-methylpyrrolidone, mixing well to obtain a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector aluminum foil, and vacuum drying at 100° C. to form a 400 μm thick carbon-sulfur composite material layer on the surface of the aluminum foil; 2) Preparation of TiO 2 -Graphene layer: TiO 2 The particles, graphene nanosheets, and binder polyvinyl alcohol are added to an organic solvent N-methylpyrrolidone and mixed to obtain a slurry, which is coated on the carbon-sulfur composite material layer and dried in vacuum at 140°C to form a 3.5 μm thick TiO 2 - graphene layer; 3) Preparation of SiO 2 - Carbon nanotube layer: SiO 2 The particles, carbon nanotubes and binder polyvinyl alcohol are added to an organic solvent N-methylpyrrolidone, mixed to obtain a slurry, and the slurry is coated on the TiO 2 -graphene layer, dried in air at 140 °C, on TiO 2 -4μm SiO2 is formed on the graphene layer 2 - Carbon nanotube layer.

[0033] The lithium-sulfur battery using the composite cathode was tested, and the first cycle discharge capacity was 1172 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 95.8%; the first cycle discharge capacity at a rate of 2C is 985mAhg -1 , the capacity retention rate is higher than 86% after 1000 cycles.

[0034] Comparative Example 1 A lithium-sulfur battery positive electrode, the preparation method is as follows: 1) Preparation of a carbon-sulfur composite material layer: adding elemental sulfur, conductive carbon black and binder polyvinyl alcohol in a mass ratio of 6:1:1 to an organic solvent N-methylpyrrolidone, mixing well to obtain a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector aluminum foil, and vacuum drying at 100° C. to form a 400 μm thick carbon-sulfur composite material layer on the surface of the aluminum foil; 2) Preparation of TiO 2 -Graphene layer: TiO 2 The particles, graphene nanosheets, and binder polyvinyl alcohol are added to an organic solvent N-methylpyrrolidone and mixed to obtain a slurry, which is coated on the carbon-sulfur composite material layer and dried in vacuum at 140°C to form a 3.5 μm thick TiO 2 - Graphene layer.

[0035] The lithium-sulfur battery using the composite cathode was tested, and the first cycle discharge capacity was 1153 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 54.6%; at a rate of 2C, the first cycle discharge capacity is 960mAhg -1 , the capacity retention rate is 42% after 1000 cycles.

[0036] Comparative Example 2 A lithium-sulfur battery positive electrode, the preparation method is as follows: 1) Preparation of a carbon-sulfur composite material layer: adding elemental sulfur, conductive carbon black and binder polyvinyl alcohol in a mass ratio of 6:1:1 to an organic solvent N-methylpyrrolidone, mixing well to obtain a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector aluminum foil, and vacuum drying at 100° C. to form a 400 μm thick carbon-sulfur composite material layer on the surface of the aluminum foil; 2) Preparation of SiO 2 - Carbon nanotube layer: SiO 2 The particles, carbon nanotubes, and binder polyvinyl alcohol were added to an organic solvent N-methylpyrrolidone and mixed to obtain a slurry. The slurry was coated on the carbon-sulfur composite material layer and dried in air at 140°C to form a 4 μm SiO 2 - Carbon nanotube layer.

[0037] The lithium-sulfur battery using the composite cathode was tested, and the first cycle discharge capacity was 1139 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 48.7%; at a rate of 2C, the first cycle discharge capacity is 937mAhg -1 , the capacity retention rate is 36.5% after 1000 cycles.

[0038] Comparative Example 3 A lithium-sulfur battery composite positive electrode, the preparation method is as follows: 1) Preparation of a carbon-sulfur composite material layer: adding elemental sulfur, conductive carbon black and binder polyvinyl alcohol in a mass ratio of 6:1:1 to an organic solvent N-methylpyrrolidone, mixing well to obtain a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector aluminum foil, and vacuum drying at 100° C. to form a 400 μm thick carbon-sulfur composite material layer on the surface of the aluminum foil; 2) Preparation of SiO 2 - Carbon nanotube layer: SiO 2 The particles, carbon nanotubes, and binder polyvinyl alcohol were added to an organic solvent N-methylpyrrolidone and mixed to obtain a slurry. The slurry was coated on the carbon-sulfur composite material layer and dried in air at 140°C to form a 4 μm SiO 2 - Carbon nanotube layer.

[0039] 3) Preparation of TiO 2 -Graphene layer: TiO 2 The particles, graphene nanosheets, and binder polyvinyl alcohol are added to an organic solvent N-methylpyrrolidone, mixed to obtain a slurry, and the slurry is coated on a SiO 2 -CNT layer, vacuum dried at 140℃, and formed a 3.5μm thick TiO 2 - Graphene layer.

[0040] The lithium-sulfur battery using the composite cathode was tested, and the first cycle discharge capacity was 1148 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 83.1%; the first cycle discharge capacity at a rate of 2C is 902mAhg -1 , the capacity retention rate is 67% after 1000 cycles.

[0041] Comparative Example 4 A lithium-sulfur battery composite positive electrode, the preparation method is as follows: 1) Preparation of a carbon-sulfur composite material layer: adding elemental sulfur, conductive carbon black and binder carboxymethyl cellulose-styrene-butadiene rubber in a mass ratio of 6:1:1 to an organic solvent N-methylpyrrolidone, mixing well to obtain a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector aluminum foil, and vacuum drying at 100° C. to form a 400 μm thick carbon-sulfur composite material layer on the surface of the aluminum foil; 2) Preparation of TiO 2 -Carbon nanotube layer: TiO 2The particles, carbon nanotubes, and binder polyvinyl alcohol were added to an organic solvent N-methylpyrrolidone and mixed to obtain a slurry. The slurry was coated on the carbon-sulfur composite material layer and dried in vacuum at 140°C to form a 6 μm thick TiO 2 - a carbon nanotube layer; 3) Preparation of SiO 2 -Graphene layer: SiO with a mass ratio of 6:1:0.8 2 The particles, graphene, and binder polytetrafluoroethylene are added to the organic solvent acetonitrile and mixed to obtain a slurry, which is then coated on the TiO 2 -CNT layer, dried in air at 120°C, on TiO 2 -1μm SiO2 is formed on the carbon nanotube layer 2 - Graphene layer.

[0042] The lithium-sulfur battery using the composite cathode was tested, and the first cycle discharge capacity was 1087 mAh g at a rate of 0.5C. -1 After 800 cycles, the capacity retention rate is 65.9%; the first cycle discharge capacity at a rate of 2C is 913mAhg -1 , the capacity retention rate after 1000 cycles is 56.9%.

[0043] It can be seen from the test results of the embodiments and comparative examples of the present invention that the lithium-sulfur battery composite positive electrode prepared based on the present invention has good stability, and the lithium-sulfur battery using the composite positive electrode has a high discharge specific capacity and a high capacity retention rate. From the comparison of the discharge specific capacity after 1000 cycles of the electrode at a 2C rate, it can be seen that the setting of the specific composite barrier layer of the present invention can significantly improve the cycle performance of the lithium-sulfur battery. It can be seen that the presence of the barrier layer can achieve nearly complete adsorption of polysulfides, greatly reducing the dissolution and migration of polysulfides in the electrolyte, which is beneficial to improving the cycle performance of the lithium-sulfur battery. From the comparison of the comparative examples, it can be seen that only one barrier layer or SiO is set first. 2 - Carbon nanotube layer and then set TiO 2 -Although the composite positive electrode of the graphene layer has a high initial discharge capacity, the battery capacity retention rate is low after long-term cycling, that is, its barrier layer has poor stability and cannot achieve long-term effective adsorption of polysulfides.

[0044] The above is a detailed introduction to a lithium-sulfur battery composite positive electrode and a lithium-sulfur battery. The above content is a further detailed description of the present invention in combination with a specific preferred embodiment, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.

Claims

1. A lithium-sulfur battery composite positive electrode, the composite positive electrode comprising a positive electrode current collector, a carbon-sulfur composite material layer located on the positive electrode current collector, and a composite barrier layer located on the carbon-sulfur composite material layer, characterized in that: The composite barrier layer consists of a TiO2-graphene layer close to the carbon-sulfur composite material layer and a SiO2-carbon nanotube layer located on the TiO2-graphene layer.

2. The lithium-sulfur battery composite positive electrode according to claim 1, characterized in that: The thickness of the TiO2-graphene layer is 0.05-5 μm, the thickness of the SiO2-carbon nanotube layer is 0.1 μm-5 μm, and the thickness of the TiO2-graphene layer is less than the thickness of the SiO2-carbon nanotube layer.

3. The lithium-sulfur battery composite positive electrode according to claim 1, characterized in that: The thickness of the carbon-sulfur composite material layer is 200-500 μm, and the mass ratio of nano-sulfur to conductive carbon black in the layer is 5-10:

1.

4. The lithium-sulfur battery composite positive electrode according to claim 1, characterized in that: The mass ratio of TiO2 to graphene in the TiO2-graphene layer is 1:2-5, and the mass ratio of SiO2 to carbon nanotubes in the SiO2-carbon nanotube layer is 2-5:

1.

5. The lithium-sulfur battery composite positive electrode according to claim 1, characterized in that: The carbon-sulfur composite material layer is composed of elemental sulfur, conductive carbon black and a binder, and the preparation method is as follows: Add elemental sulfur, conductive carbon black and a binder into an organic solvent, mix well to obtain a positive electrode slurry, apply the positive electrode slurry on a positive electrode collector, and dry in vacuum at 80-100° C. to form a carbon-sulfur composite material layer on the surface of the positive electrode collector; the mass ratio of the elemental sulfur, conductive carbon black and binder is 5-10:1:0.5-1.

6. The lithium-sulfur battery composite positive electrode according to claim 1, characterized in that: The TiO2-graphene layer preparation method is as follows: TiO2 particles, graphene nanosheets and a binder are added to an organic solvent and mixed to obtain a slurry, the slurry is coated on a carbon-sulfur composite material layer, and vacuum dried at 100-150°C to obtain a composite material; the mass ratio of the TiO2 particles, graphene nanosheets and the binder is 1:2-5:0.5-1.

7. The lithium-sulfur battery composite positive electrode according to claim 1, characterized in that: The SiO2-carbon nanotube layer preparation method is as follows: Add SiO2 particles, carbon nanotubes and a binder into an organic solvent, mix well to obtain a slurry, apply the slurry on a TiO2-graphene layer, and dry in air at 100-150°C to obtain a SiO2-graphene layer; the mass ratio of the SiO2 particles, carbon nanotubes and binder is 2-5:1:0.5-1.

8. The lithium-sulfur battery composite positive electrode according to any one of claims 5 to 7, characterized in that: The binder is one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose-styrene-butadiene rubber and polyvinyl alcohol, and the organic solvent is one of N-methyl pyrrolidone, acetonitrile and acetone.

9. A lithium-sulfur battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode is the composite positive electrode according to any one of claims 1 to 8.

10. A method for preparing a lithium-sulfur battery composite positive electrode according to any one of claims 1 to 8, characterized in that: The steps include: 1) Preparation of a carbon-sulfur composite material layer: adding elemental sulfur, conductive carbon black and a binder in a mass ratio of 5-10:1:0.5-1 to an organic solvent, mixing well to obtain a positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector aluminum foil, and vacuum drying at 80-100° C. to form a carbon-sulfur composite material layer of 200-500 μm thick on the surface of the aluminum foil; 2) Preparing a TiO2-graphene layer: adding TiO2 particles, graphene nanosheets, and a binder in a mass ratio of 1:2-5:0.5-1 to an organic solvent, mixing to obtain a slurry, coating the slurry on the carbon-sulfur composite material layer, and vacuum drying at 100-150° C. to form a 0.05-5 μm thick TiO2-graphene layer on the carbon-sulfur composite material layer; 3) Preparing a SiO2-carbon nanotube layer: adding SiO2 particles, carbon nanotubes, and a binder in a mass ratio of 2-5:1:0.5-1 to an organic solvent, mixing to obtain a slurry, coating the slurry on the TiO2-graphene layer, and drying in air at 100-150° C. to form a SiO2-carbon nanotube layer on the TiO2-graphene layer that is 0.1 μm to 5 μm thicker than the TiO2-graphene layer; The binder is one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose-styrene-butadiene rubber and polyvinyl alcohol, and the organic solvent is one of N-methyl pyrrolidone, acetonitrile and acetone.

Citation Information

Patent Citations

  • Three-dimensional ordered porous sulfur-carrying material for positive pole piece of lithium-sulfur battery as well as preparation method and application of three-dimensional ordered porous sulfur-carrying material

    CN111370667A

  • Preparation method of covalent organic framework enhanced gel electrolyte for lithium-sulfur battery

    CN116845352A

  • Preparation method of high-entropy monatomic catalyst modified diaphragm and application of high-entropy monatomic catalyst modified diaphragm in lithium-sulfur battery

    CN117335094A

  • Lithium-sulfur battery interlayer material, preparation method thereof and lithium-sulfur battery

    CN118017049A

  • Preparation method of graphene / titanium oxide composite material and application method thereof

    CN104600267A